Handling performance control for hybrid 8-wheel-drive vehicle and simulation verification. Issue 8 (2nd August 2016) - Ni, Jun; Hu, Jibin
ABSTRACT: In order to improve handling performance of a hybrid 8-Wheel-Drive vehicle, the handling performance control strategy was proposed. For armoured vehicle, besides handling stability in high speed, the minimum steer radius in low speed is also a key tactical and technical index. Based on that, the proposed handling performance control strategy includes 'Handling Stability' and 'Radius Minimization' control modes. In 'Handling Stability' control mode, 'Neutralsteer Radio' is defined to adjust the steering characteristics to satisfy different demand in different speed range. In 'Radius Minimization' control mode, the independent motors are controlled to provide an additional yaw moment to decrease the minimum steer radius. In order to verify the strategy, a simulation platform was built including engine and continuously variable transmission systems, generator and battery systems, independent motors and controllers systems, vehicle dynamic and tyre mechanical systems. The simulation results show that the handling performance of the vehicle can be enhanced significantly, and the minimum steer radius can be decreased by 20% which is significant improvement compared to the common level of main battle armoured vehicle around the world.